Examination of the Solvency of a Company in an International Accounting Environment - Szekeres, Alexandra; Dékán Tamásné Orbán, Ildikó (International Journal of Engineering and Management Sciences, 2018)
It is highly important for every business to be solvent for both short and long term. Solvency is a prerequisite for the operation of a company, especially short term solvency, also known as liquidity. Liquidity plays a prominent role in the life of a given business. For this it is important for a business to strive to avoid liquidity problems. In the present article we examine the short term solvency of an American corporation, which prepares its financial statements according to the US GAAP (The United States Generally Accepted Accounting Principles). We present the fundamental short term solvency ratios, and the subsequent conclusions. Since for the calculation of the ratios the data of the examined company’s financial statement is needed, which shows differences from the yearly report of a Hungarian company, in the article we will also discuss the differences between the two accounting systems with regard to those items, which have an effect on the liquidity ratios, in particular current assets and short-term liabilities.